Noninvasive Pediatric Liver Fibrosis Measurement: Two-Dimensional Shear Wave Elastography Compared With Transient Elastography - Tran, Léa Chantal; Ley, Delphine; Bourdon, Gurvan; Coopman, Stéphanie; Lerisson, Héloïse; Tillaux, Céline; Béhal, Hélène; Gottrand, Frédéric; Aumar, Madeleine (Frontiers in Pediatrics, 2022)
Objectives Although transient elastography (TE) is the primary noninvasive method for assessing liver fibrosis, its use remains to be validated in children. This study aims to evaluate the agreement between two-dimensional ultrasound shear wave elastography (2D-SWE) and TE to assess pediatric liver stiffness method. Methods During the 18-month study, we prospectively included 101 consecutive children (median age: 8.5 years, range: 1 month to 17 years) who required TE for medical reasons, and in whom 2D-SWE measurement was performed within a 3-month follow-up during a routine ultrasound. Liver elasticity values were classified according to the Metavir score using published pediatric norms for TE and according to the manufacturer's reference values for 2D-SWE. The Spearman's correlation coefficient was used to assess the relationship between the elasticity measured by the two techniques. Concordance was described by the Bland–Altman method. Results A strong correlation (rho = 0.70, p < 0.001) was found between 2D-SWE and TE for the elasticity measures. The strength of correlation was higher among patients older than 6 years (rho = 0.79, p < 0.001). Concordance between liver fibrosis stages assessed by these techniques was moderate [weighted kappa = 0.46, (95% CI: 0.35–0.57)]. When considering stages over F2, 2D-SWE diagnostic performances showed a sensitivity of 85% (95% CI: 74–92) and a specificity of 57% (95% CI: 42–70) compared with TE. Conclusion Measurements of the liver stiffness using 2D-SWE and TE are strongly correlated. The moderate concordance between these techniques for assessing the liver fibrosis stage provides evidence against alternating between these methods during follow-up of patients with the chronic liver diseases.